Superwetting polyethersulfone membrane functionalized with ZrO2 nanoparticles for polycyclic aromatic hydrocarbon removal. (30th January 2022) - Chen, Xiujuan; Huang, Guohe; An, Chunjiang; Feng, Renfei; Wu, Yinghui; Huang, Charley
Graphical abstract: Highlights: A superwetting PES-PAA-ZrO2 nanofiltration membrane was proposed for PAH removal. The initial water contact angle was less than 10° and dropped to 0° within 1 s. The wastewater treatment efficiency was increased by about 4 times. The mechanism of ZrO2 immobilization was revealed through synchrotron-based analysis. Abstract: Polycyclic aromatic hydrocarbons (PAHs) are persistent and widespread in the aquatic environment, causing potential hazards for human health. In this study, a superwetting and robust PES-PAA-ZrO2 nanofiltration membrane was proposed through surface modification for PAH removal with high efficiency. A ZrO2 coating was formed on polyethersulfone (PES) membrane surface through chemical bonding, thus the PES-PAA-ZrO2 membrane exhibited super-hydrophilicity, under-water oleophobicity, and excellent stability. In comparison with the original PES membrane, the water contact angle of the modified membrane was significantly decreased from about 50° to less than 10°, and quickly dropped to 0° within 1 s. This provided a much lower energy barrier for water permeation due to its super-high water affinity. The wastewater treatment efficiency was increased by about 4 times after modification with more than 90% of PAH rejection rate. The excellent robustness of PES-PAA-ZrO2 membrane was verified under various conditions, which gave the membrane practical potential for long-term operation.